The problems of retrofitting of dwellings / Gyvenamųjų namų apšiltinimo problemos - Stankevičius, V.; Burlingis, A. (Journal of Civil Engineering and Management, 1996)
With the rise of energy prices, the need for saving energy have increased. The existing buildings are poorly insulated, so it seems enough to insulate building envelope additionally and in such a way to save about 50% of annual energy consumption for heating. But there are some problems here. With new constructions everything is clear—the insulating materials do not enlarge the overall cost of building too much. But the situation becomes much more complicated with the existing poorly insulated buildings. The profitability of energy savings in dwelling buildings depends on the relationship between the prices of energy, building materials and workmanship, the market lowest interest rate and partly on average earnings of the inhabitants. The paper submits the data of Lithuania's dwelling stock—thermal conditions of enclosures, dwelling areas, annual average heat losses before and after insulation of enclosures according to the requirements of the building code RSN-143-92 “Thermal Technique of Buildings”. We have also calculated the limit investments into additional insulation of enclosures, depending on duration of a bank loan, a bank interest rate, present price of heating and expected probable relative energy price increase in Lithuania. The paying back energy conservation measures and priorities of realization of those measures are suggested under Lithuanian conditions too.Article in Lithuanian.First Published Online: 26 Jul 2012